Adaptive benefit of cross-modal plasticity following cochlear implantation in deaf adults - Anderson, Carly A.; Wiggins, Ian M.; Kitterick, Pádraig T.; Hartley, Douglas E.H. (National Academy of Sciences, 2017)
It has been suggested that visual language is maladaptive for hearing restoration with a cochlear implant (CI) due to cross-modal recruitment of auditory brain regions. Rehabilitative guidelines therefore discourage the use of visual language. However, neuroscientific understanding of cross-modal plasticity following cochlear implantation has been restricted due to incompatibility between established neuroimaging techniques and the surgically implanted electronic and magnetic components of the CI. As a solution to this problem, here we used functional near-infrared spectroscopy (fNIRS), a noninvasive optical neuroimaging method that is fully compatible with a CI and safe for repeated testing. The aim of this study was to examine cross-modal activation of auditory brain regions by visual speech from before to after implantation and its relation to CI success. Using fNIRS, we examined activation of superior temporal cortex to visual speech in the same profoundly deaf adults both before and 6 mo after implantation. Patients’ ability to understand auditory speech with their CI was also measured following 6 mo of CI use. Contrary to existing theory, the results demonstrate that increased cross-modal activation of auditory brain regions by visual speech from before to after implantation is associated with better speech understanding with a CI. Furthermore, activation of auditory cortex by visual and auditory speech developed in synchrony after implantation. Together these findings suggest that cross-modal plasticity by visual speech does not exert previously assumed maladaptive effects on CI success, but instead provides adaptive benefits to the restoration of hearing after implantation through an audiovisual mechanism.